Determination of Age from Shoulder Joint by Radiological Examination of Epiphyseal Union of Proximal End of Humerus in Boys from Ahmedabad Region (Indian Journal of Forensic Medicine & Toxicology, 2021)
In law, crime and punishment is entirely based on criminal responsibility and this in turn depends on theage of a person. It is well known that appearance and fusion of epiphysis of long bone occurs at particularperiod of time and this in turns help in age estimation. As there is variation in appearance and fusion time ofepiphysis, aim of the present study is to determine Epiphyseal union of proximal end of humerus in boys inAhmedabad region. Present study was conducted by department of Forensic Medicine and Toxicology, B.J.Medical College Ahmedabad. Total 100 boys of age group between 14-20 years were included in the studyand were subjected for radiological examination. To study the appearance and fusion of ossification centreof upper end of humerus digital X-ray with AP view was taken. Result was tabulated and statistical analysisof result was done comparing with previous studies.
Keywords: Age estimation. Epiphyseal Union, boys, proximal end of humerus, shoulder joint